Penggunaan Cyclone Ventilator sebagai Kincir Angin penggerak Generator: Bachtera Indarto, Achaddiad, Susilo Indrawati, Didiek B Rahmat, Hasto Sunarno - Bachtera Indarto, Bachtera Indarto; Achaddiad, Achaddiad; Susilo Indrawati, Susilo Indrawati; Didiek Basuki Rachmad, Didiek Basuki Rachmad; Hasto Sunarno, Hasto Sunarno (Jurnal Fisika dan Aplikasinya, 2025)
The research has been conducted using the generator ceiling fan 12W, the number of gear are 35 and 60 as well as the number of gear cyclone ventilator is 95. At the same wind speed at the generator shaft speed gear pair 95/35 is greater than that 95/60. The output voltage generator for gear pair 95/35 is larger than gear pair 95/60. In the gear pair 95/35 generator power output of 2.0 mW at a wind speed is 4.0 m/s and spindle speed is 40.2 rpm .